Mesentero-axial gastric volvulus in an old woman: a case report of a diagnostic challenge - Balzano, Rosario Francesco; Testini, Valentina; Lattanzio, Francesco; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Gastric volvulus is a rare conditiom defined as an abnormal rotation of the stomach around itself. Acute gastric volvulus is a surgical emergency because it is a life-threatening condition, but its non-specific symptoms make diagnosis difficult. There are two types of gastric volvulus: organoaxial and mesentero-axial. The treatmet is surgical intervention. Computed tomography allows to identify and classify gastric volvulus and rule out complications so that to guide surgery management. We report a case of a mesentero-axial gastric volvulus in an old woman with abdominal pain, who underwent surgery in laparoscopy.